Windows Server 2016 automation with PowerShell cookbook : automate manual administrative tasks with ease - Lee, Thomas, 1950- (Packt Publishing, 2017)
Over 100 recipes to help you leverage PowerShell to automate Windows Server 2016 manual tasks About This Book Automate Windows server tasks with the powerful features of the PowerShell Language Master new features such as DevOps, containers, and Nano servers, and speed up their performance using PowerShell Improve PowerShell's usability, and control and manage Windows-based environments by working through inviting recipes Who This Book Is For If you are a systems administrator, engineer, or an architect working with Windows Server 2016 and want to automate tasks with PowerShell, then this book is for you. A basic knowledge of PowerShell is expected. What You Will Learn Streamline routine administration processes Improve the performance and storage of your Windows server with enhanced large-scale PowerShell scripts Use DSC to leverage Windows server features Generate automatic reports that highlight unexpected changes in your environment Monitor performance and report on system utilization using detailed graphs and analysis Create and manage a reliable and redundant Hyper-V environment Manage your enterprise's patch level Utilize multiple tools and protocols to manage your environment In Detail This book showcases several ways that Windows administrators can use to automate and streamline their job. You'll start with the PowerShell and Windows Server fundamentals, where you'll become well versed with PowerShell and Windows Server features. In the next module, Core Windows Server 2016, you'll implement Nano Server, manage Windows updates, and implement troubleshooting and server inventories. You'll then move on to the Networking module, where you'll manage Windows network services and network shares. The last module covers Azure and DSC, where you will use Azure on PowerShell and DSC to easily maintain Windows servers. Style and approach This is a practical guide packed with attractive recipes to help you effectively use PowerShell to accelerate your daily administrative tasks with Windows server.